2020
DOI: 10.1167/iovs.61.6.20
|View full text |Cite
|
Sign up to set email alerts
|

Role of TH17 Responses in Increasing Herpetic Keratitis in the Eyes of Mice Infected with HSV-1

Abstract: PURPOSE. T H 17 cells play an important role in host defense and autoimmunity yet very little is known about the role of IL17 in herpes simplex virus (HSV)-1 infectivity. To better understand the relationship between IL17 and HSV-1 infection, we assessed the relative impact of IL17A-deficiency and deficiency of its receptors on HSV-1 responses in vivo. METHODS. We generated IL17RA −/− and IL17RA −/− RC −/− mice in-house and infected them along with IL17A −/− and IL17RC −/− mice in the eyes with 2 × 10 5 PFU/ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 115 publications
(187 reference statements)
0
4
0
Order By: Relevance
“…Since IL-17A binds to both IL-17RA and IL-17RC, detection of demyelination in IL-17RA -/- and IL-17RC -/- mice may suggest that the other receptor compensates for the missing receptor for binding to IL-17A. Thus, to determine if the absence of both RA and RC molecules is required to block CNS demyelination in infected mice, we generated mice lacking a combination of both IL-17RA and IL-17RC as we described previously ( 41 ). We infected IL-17RA -/- RC -/- mice with HSV-IL-2 and looked for demyelination in optic nerve, brain, and spinal cord sections of infected mice as above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since IL-17A binds to both IL-17RA and IL-17RC, detection of demyelination in IL-17RA -/- and IL-17RC -/- mice may suggest that the other receptor compensates for the missing receptor for binding to IL-17A. Thus, to determine if the absence of both RA and RC molecules is required to block CNS demyelination in infected mice, we generated mice lacking a combination of both IL-17RA and IL-17RC as we described previously ( 41 ). We infected IL-17RA -/- RC -/- mice with HSV-IL-2 and looked for demyelination in optic nerve, brain, and spinal cord sections of infected mice as above.…”
Section: Resultsmentioning
confidence: 99%
“…IL-17RC -/- mice were developed by Genentech and were obtained from the Mutant Mouse Regional Resource Center (University of California, Davis). IL-17RA -/- and IL-17RA -/- RC -/- were developed in our Lab and described previously ( 41 ). IL-17RD -/- mice were obtained from the Mutant Mouse Regional Resource Center (University of California, Davis).…”
Section: Methodsmentioning
confidence: 99%
“…This may be due to its selective autophagy regulatory properties. Hirose et al [ 200 ] investigated the role of TH17 responses in an HSV-1-infected murine model and concluded that interleukin-17 protects against ocular morbidity secondary to HSV-1[ 200 ].…”
Section: Immune Responses In Herpes Simplex Keratitis: Implications F...mentioning
confidence: 99%
“…Similarly, IL17RD (P10) also regulates JNK signaling and TLR signaling (Girondel and Meloche, 2021). Additionally the IL17 receptor has been ascribed a role in HSV-1 infection (Hirose et al, 2020). FLT1 (P14) activates the MAPK signaling pathway and its expression is increased in HSV-infected sensory neurons (Kramer et al, 2003).…”
Section: Variants In Innate and Adaptive Signaling Pathwaysmentioning
confidence: 99%